In Vitro Long-Term Expansion and High Osteogenic Potential of Periodontal Ligament Stem Cells: More Than a Mirage. Issue 1 (January 2019) - Di Vito, Anna; Giudice, Amerigo; Chiarella, Emanuela; Malara, Natalia; Bennardo, Francesco; Fortunato, Leonzio
The periodontal ligament displays a reservoir of mesenchymal stem cells which can account for periodontal regeneration. Despite the numerous studies directed at the definition of optimal culture conditions for long-term expansion of periodontal ligament stem cells (PDLSCs), no consensus has been reached as to what is the ideal protocol. The aim of the present study was to determine the optimal medium formulation for long-term expansion and stemness maintenance of PDLSCs, in order to obtain a sufficient number of cells for therapeutic approaches. For this purpose, the effects of three different culture medium formulations were evaluated on PDLSCs obtained from three periodontal ligament samples of the same patient: minimum essential medium Eagle, alpha modification (α-MEM), Dulbecco's modified Eagle's medium (DMEM), both supplemented with 10% fetal bovine serum (FBS), and a new medium formulation, Ham's F12 medium, supplemented with 10% FBS, heparin 0.5 U/ml, epidermal growth factor (EGF) 50 ng/ml, fibroblast growth factor (FGF) 25 ng/ml, and bovine serum albumin (BSA) 1% (enriched Ham's F12 medium; EHFM). PDLSCs grown in EHFM displayed a higher PE-CD73 mean fluorescence intensity compared with cells maintained in α-MEM and DMEM, even at later passages. Cells maintained in EHFM displayed an increased population doubling and a reduced population doubling time compared with cells grown in DMEM or α-MEM. α-MEM, DMEM and EHFM with added dexamethasone, 2-phospho-L-ascorbic acid, and β-glycerophosphate were all able to promote alkaline phosphatase activity; however, no calcium deposition was detected in PDLSCs cultured in EHFM-differentiation medium. When EHFM-, α-MEM- and DMEM-expanded PDLSCs were transferred to a commercial culture medium for the osteogenesis, mineralization became much more evident in confluent monolayers of EHFM-expanded PDLSCs compared with DMEM and α-MEM. The results suggest EHFM is the optimal medium formulation for growth and stemness maintenance of primary PDLSCs. Moreover, EHFM confers higher osteogenic potential to PDLSCs compared with cells maintained in the other culture media. Overall, the results of the present work confirmed the advantages of using EHFM for long-term expansion of mesenchymal cells in vitro and the preservation of high osteogenic potential.